(untitled) (Bangladesh Journal of Agricultural Research, 2017)
The present study evaluated the efficacy of some new generation insecticides namely Clothianidin 48 SC, Fenpyroximate 5 SC, Pyridaben 20 WP and Methoxyphenozide 24 SC along with a synthetic pyrethroid insecticide, Fenpropathrin 20 EC against mustard aphid and their effects on beneficial insects i.e. syrphid flies and foraging honeybees during 2015 - 2016 in Bangladesh Agricultural Research Institute, Gazipur, Bangladesh. Tested six treatments were: Clothianidin 48 SC 1ml l-1, Fenpyroximate 5 SC 0.25 ml l-1, Pyridaben 20 WP 1g l-1, Methoxyphenozide 24 SC 1ml l-1 , Fenpropathrin 20 EC 1ml l-1 and an untreated control, replicated three times in RCBD. It was found that, Methoxyphenozide 24 SC was found to be the most effective against aphid offering lower aphid population (1.42/ top 10 cm central twig) at 7 days after spraying (DAS) which was statistically identical to Clothianidin 48 SC (1.50/top 10 cm central twig). Among the insecticides, Methoxyphenozide 24 SC was also found to be safer to the populations of syrphid flies revealing flight activity of 6.85 adults (plot/5 min) and honeybees of 8.82 workers (plot/5 min), respectively at 7 DAS. Whereas, Clothianidin 48 SC and Pyridaben 25 WP treated plots were found to be highly toxic to these beneficial insects. Consequently, the highest yield was obtained from Methoxyphenozide 24 SC (1.55 t/ha) followed by Fenpyroximate 5 SC (1.42 t/ha) treated plots. Bangladesh J. Agril. Res. 42(3): 563-570, September 2017